Aile Mutluluğunu Etkileyen Sosyo-kültürel Değişkenlerin Din Eğitimi Açısından Değerlendirilmesi: Samsun İli Örneği - Varol, Kübra (Ondokuz Mayıs Üniversitesi, Sosyal Bilimler Enstitüsü, 2006)
XII ÖZET Araştırma aile mutluluğu üzerinde etkili olan sosyo-kültürel faktörleri araştırmak ve elde edilen bulguları din eğitimi açısından değerlendirmek amacıyla düzenlenmiştir. Araştırmanın evreni 2004-2005 yıllarında Samsun il sınırları içinde ikamet eden evli çiftlerden oluşmaktadır. Araştırmanın örneklemini ise tesadüfi yöntemle belirlenmiş 153 evli kişi temsil etmektedir. Araştırmada eşlerin aile mutlulukları üzerinde etkili olduğu düşünülen cinsiyet yaş, eğitim durumu, evlenme yaşı, aylık gelir, evlenme şekli, evlilik durumu (evlilik sayısı), çocuğun olup olmaması, kaç çocuk olduğu, çocukların cinsiyeti, süreğen hasta ya da engelli çocuğun olup olmaması, dindarlık algısı, dini bilgilerin genel olarak almış yeri aile yapısı, meslek ve sağlık durumu olmak üzere 16 sosyo-kültürel etken ele alınmıştır. Araştırmada elde edilen verilerin istatistiksel analizi SPSS (Statiscal Package for Social Sciences) paket programı ile yapılmıştır. Hipotezlerin test edilmesinde varyans analizi (ANOVA-F testi) kullanılmıştır. Sonuç olarak elde edilen bulgular ışığında, yaş, eğitim durumu evlenme şekli ve çocuğun olup olmaması falctörlerinin eşlerin aile mutluluğu üzerinde etkili olduğu tespit edilmiştir. Anahtar Kelimeler: Aile, Din Eğitimi, Mutluluk, Aile Mutluluğu

xni ABSTRACT The Evaluation of Some Socio-Cultural Factors Affecting the Happiness of Family in Terms of Religious Education: The Case of Samsun The aim of this study is to examine the socio-cultural factors affecting on the happiness of family and then to evaluate these findings in terms of religious education. The study covers the married couples living in the borders of Samsun in 2004- 2005. The sample of the study contains 153 married individuals. These people were selected by random technique. In the study sixteen independent variables were used. These independent variables are the following: Sex, age, the level of education, the age of marriage, monthly salary, the style of marriage, the number of marriage, whether having a child or not, the number of children, the sexes of children, whether the children have a handicap, the understanding of religion, the place of receiving religious education, the structure of family, occupation and general health situation. In order to test the level of family happiness, two questionnaires, the questionnaire of personal questions and the questionnaire of family happiness developed by the researcher herself, were used. For the analyzing the findings, the SPPS (Statistical Package for Social Sciences) was used. In addition, to test the significance of relationships of the various categories of the sample, the ANOVA-F was used. It was found that some factors such as the age, the level of education, the style of marriage, whether having a child or not were found as statistically significant. Kew Words: Family, Religious Education, Happiness, Family Happiness
The Evaluation of Some Socio-Cultural Factors Affecting the Happiness of Family in Terms of Religious Education: the Case of Samsun
Tez (yüksek lisans) -- Ondokuz Mayıs Üniversitesi, 2006
Libra Kayıt No: 17235
Keywords: Religion; Din; TEZ YÜK LİS V323a 2006